A novel human specific lncRNA MEK6-AS1 regulates adipogenesis and fatty acid biosynthesis by stabilizing MEK6 mRNA - Di Li; Yunhua Chen; Xingyu Zhu; Yanlei Yang; Hongling Li; Robert Chunhua Zhao (Journal of Biomedical Science)
Abstract Background Obesity is becoming one of the major non-communicable diseases with increasing incidence and risks that cannot be ignored. However effective and safe clinical treatment strategies still need to be deeply explored. Increased number and volume of adipocytes lead to overweight and obesity. The aim of our work is to identify lncRNAs that have important regulatory in differentiation of human mesenchymal stem cells (MSCs) into adipocytes, and to provide effective targets for clinical prevention and treatment of obesity and related metabolic disorders. Methods We extracted primary MSCs from human adipose tissue, and conducted expression profile analysis of lncRNAs during adipogenic differentiation of MSCs to screen changed lncRNAs. Characteristics of lncRNA were revealed mainly by RACE and RNA FISH. Loss- and gain-of function experiments in vivo and in vitro were used to analyze effects of lncRNA. Targeted metabolomics was utilized to detect levels of free fatty acids. RNA pull-down, mRNA stability tests, etc. were employed to explore mechanisms of lncRNA. Results Human-specific lncRNA, we named it MEK6-AS1, was the most up-regulated transcript during adipogenic differentiation of MSCs. MEK6-AS1 was highly expressed in adipose tissue samples from individuals with BMI ≥ 25 and positively correlated with adipogenic marker genes in these samples. Knocking down lncRNA inhibited expression of adipogenic differentiation markers and ectopic adipogenesis, reducing contents of various free fatty acids, as well as promoting osteogenic differentiation. Overexpression of lncRNA had the opposite effects to the above processes. We also found that MEK6-AS1 was elevated during hepatic steatosis organoid generation. Mechanistically, MEK6-AS1 worked partially through stabilization of MEK6 mRNA by NAT10. Conclusions We have identified a human-specific lncRNA (MEK6-AS1) with position information in the genomic database but has not been extensively reported. We demonstrated that MEK6-AS1 as a novel lncRNA involved in adipogenic differentiation and adipogenesis, fatty acid metabolism, and osteogenic differentiation. We found that MEK6-AS1 may exert its effect by enhancing MEK6 mRNA stability through NAT10. Our study may provide insights into implication of lncRNAs in stem cell biology and offer a new potential therapeutic target for the prevention and treatment of obesity and other related disease.